2011
DOI: 10.1186/1475-925x-10-13
|View full text |Cite
|
Sign up to set email alerts
|

A framework for automatic heart sound analysis without segmentation

Abstract: BackgroundA new framework for heart sound analysis is proposed. One of the most difficult processes in heart sound analysis is segmentation, due to interference form murmurs.MethodEqual number of cardiac cycles were extracted from heart sounds with different heart rates using information from envelopes of autocorrelation functions without the need to label individual fundamental heart sounds (FHS). The complete method consists of envelope detection, calculation of cardiac cycle lengths using auto-correlation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…Using this algorithm there was no need to label the individual Fundamental Heart Sounds (FHS) for extraction of individual heart cycles. Discrete wavelet transform was used for feature extraction of cardiac sounds and classification was done using neural network bragging predictors [7]. In 2011, Sanei et al used Adaptive Singular Spectrum Analysis (ASSA) to separate murmurs from the recorded heart sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Using this algorithm there was no need to label the individual Fundamental Heart Sounds (FHS) for extraction of individual heart cycles. Discrete wavelet transform was used for feature extraction of cardiac sounds and classification was done using neural network bragging predictors [7]. In 2011, Sanei et al used Adaptive Singular Spectrum Analysis (ASSA) to separate murmurs from the recorded heart sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Babaei et al [17] utilized the main statistical characteristics of PCG signals such as mean and standard deviation in different level of DWT decomposition and acquired 94.24% accuracy for classifying AR, AS and PS (pulmonary stenosis). A framework was proposed by Yuenyong et al [6] based on DWT and without segmentation, for heart sound classification and gained 92% accuracy to classify a number of different heart valve disorders. Studies were reported by Choi et al [2], [10] based on WPT for classifying heart sounds.…”
Section: Constructing the Hybrid Classifiermentioning
confidence: 99%
“…identification of the first and the second heart sound (S1 & S2). There are a number of researches that were addressed PCG segmentation [4], [5], although some works were reported for classifying heart sound without segmentation [6]- [8]. In order to extract discriminant features, an appropriate signal analysis technique is required.…”
Section: Introductionmentioning
confidence: 99%
“…Some segmentation approaches use envelope extraction based on wavelet transform to gain the frequency characteristics of S1 and S2 sound [6]. In the second type approaches, abnormal PCG records are detected without segmentation [7,8].…”
Section: Introductionmentioning
confidence: 99%